Pembelajaran Fisika Berbantuan Alat Peraga Proyektor Smartphone untuk Meningkatkan Pemahaman Konsep Optik pada Siswa SMP (UPEJ Unnes Physics Education Journal, 2018)
Device props that developed is smartphone projector that was equipped by student work sheets. Smartphone projector props from simple materials and easy to find intheform of a water-filled bulb that the system works like a convex lens, so it can produce real, inverted, and zoomed in shadow properties. Student work sheets as a supplement containing the props instruction, material reviews, and evaluation questions. The result of feasibility test of practicum device categorized as very high with percentage 87.64%. Research and Development in the form of Pretest and Postest One Group Design carried out for thr test of respondents. This research was held in junior high school 3 Juwana. The effectiveness test analysis was performed by the N-Gain <g> test and questionnaire student response. Validation results by validators for smartphone projector with student work sheets showed average score of 87.64%, so the tool props are very suitable to use as instructional media. N-Gain test analysis showed pretest-posttest results were classified as medium criterion with a <g> value of 0.589 and 82.35% classical completeness that is high. The results of the analysis of student responses show the value of 78.76 with positive criteria